Repeated centralized multidisciplinary team assessment of resectability, clinical behavior, and outcomes in 1086 Finnish metastatic colorectal cancer patients (RAXO): A nationwide prospective intervention study - Osterlund Pia; Salminen Tapio; Soveri Leena-Maija; Kallio Raija; Kellokumpu Ilmo; Lamminmäki Annamarja; Halonen Päivi; Ristamäki Raija; Lantto Eila; Uutela Aki; Osterlund Emerik; Ovissi Ali; et al. (ELSEVIER, 2022)
Background: Resection of colorectal cancer (CRC) metastases provides good survival but is probably underused in real-world practice.
Methods: A prospective Finnish nationwide study enrolled treatable metastatic CRC patients. The intervention was the assessment of resectability upfront and twice during first-line therapy by the multidisciplinary team (MDT) at Helsinki tertiary referral centre. The primary outcome was resection rates and survival.
Findings: In 2012-2018, 1086 patients were included. Median follow-up was 58 months. Multiple metastatic sites were present in 500 (46%) patients at baseline and in 820 (76%) during disease trajectory. In MDT assessments, 447 (41%) were classified as resectable, 310 (29%) upfront and 137 (18%) after conversion therapy. Sixhundred and ninety curative intent resections or local ablative therapies (LAT) were performed in 399 patients (89% of 447 resectable). Multiple metastasectomies for multisite or later developing metastases were performed in 148 (37%) patients. Overall, 414 liver, 112 lung, 57 peritoneal, and 107 other metastasectomies were performed. Median OS was 80.4 months in R0/1-resected (HR 0.15; CI95% 0.12-0.19), 39.1 months in R2-resected/LAT (0.39; 0.29-0.53) patients, and 20.8 months in patients treated with "systemic therapy alone" (reference), with 5-year OS rates of 66%, 40%, and 6%, respectively.
Interpretation: Repeated centralized MDT assessment in real-world metastatic CRC patients generates high resectability (41%) and resection rates (37%) with impressive survival, even when multisite metastases are present or develop later.